FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEIKUTSERTAAN WUS (WANITA USIA SUBUR) DALAM PEMERIKSAAN IVA (INSPEKSI VISUAL ASAM ASETAT) TAHUN 2021 - Febriyanti Marantika; Isrowiyatun Daiyah; Ahmad Rizani (Jurnal Inovasi Penelitian, 2022)
Ca. Cervix or cervical cancer ranks second in cancer to women after breast cancer. According to WHO (World Health Organization), 490,000 in the world each year are diagnosed with Ca. Cervix and 80% are in developing countries including Indonesia. Cervix can be done with a screening program through a method that is cheaper, easier, and simpler but has a fairly high diagnostic accuracy among others, by effort to get more early Ca. Cervix findings through visual inspection by applying acidic applications acetate as know as IVA examination. The factors that influence women of childbearing age in doing IVA examination include age, knowledge, parity, and attitude. The purpose of this study was to determine the factors that influence the participation of women of childbearing age in the IVA examination. Sources of data were obtained from 9 journals, consisting of 7 national journals and 2 international journals. Based on the literature study conducted, it was concluded that age (100%), knowledge (100%), parity (60%), and husband’s support (67%) were factors that influenced the participation of women of childbearing age (WUS) in carrying out IVA examinations